Investigating the Effectiveness of Cognitive- Behavioral Therapy on Reducing Driving Phobia and Driving Cognitions in Women Living in Shiraz - Azimi, Negin; Zargar, Yadollah; Davoudi, Iran (International Journal of Psychosocial Rehabilitation, 2020)
In the present study, the effectiveness of cognitive-behavioral therapy on reducing driving phobia and driving cognitions in women living in Shiraz was investigated. The design of this study was experimental with pre-test and post-test with a control group. First, using a convenience sampling method, 40 people completed two questionnaires, including driving cognition and driving situations questionnaire. In the second step, 30 people who had higher scores with a diagnosis of driving phobia, were randomly assigned to two groups (experimental and control) after being interviewed. The experimental group received individual treatment for 12 sessions. Data were analyzed using SPSS16 software. The results of multivariate analysis of variance (MANCOVA) showed that cognitive-behavioral therapy significantly reduced driving phobia and driving cognitions in the experimental group compared to the control group (p